Imidazolium-based ionic liquid as a green solvent for the Heck reaction between iodobenzene and styrene - Son Nam, Phan Thanh; My Hien, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
An easily accessible ionic liquid, 1-hexyl-3-methylimidazolium bromide, was synthesized from n-hexyl bromide and N-methylimidazole under microwave irradiation condition, and characterized by 1H and 13C NMR, and MS. The ionic liquid was demonstrated to be an efficient and recyclable solvent for the Heck cross-coupling reaction between iodobenzene and styrene to form trans-stilbene as the principal product. The reaction was performed in the ionic liquid, using 5 mol% of PdCl2 at 140oC in the presence of triethylamine as the base. Reaction conversions of 60% and 97% were achieved after 7 hours, without and with using triphenylphosphine as an additive, respectively. The ionic liquid – PdCl2 system could be reused in subsequent reaction without significant degradation in activity. Furthermore, using the ionic liquid as the reaction solvent in conjunction with microwave irradiation, the reaction rate was dramatically enhanced, with 98% conversion being achieved within 2 minutes.